Clinical audit as a quality improvement tool in the Gaza Strip: an audit of audits. (July 2021) - Alyacoubi, Said; Böttcher, Bettina; Albarqouni, Loai; Elessi, Khamis
Abstract: Background: Clinical audit plays a fundamental role in improving the quality of patient care and hence, is considered a cornerstone of clinical governance. This quality improvement tool is newly introduced in the health-care system of the Gaza Strip. Although the number of audits completed in Gaza has been increasing over the past few years, little evidence is available of subsequent quality improvements in practice. Methods: An online survey was used to collect information on the audit team, location, applied methods, outcomes, presentation of data, and reaudit. Medical students and health-care professionals who had conducted audits between 2015 and 2018 were invited to complete the survey from Oct 12 to Nov 2, 2018. Findings: Data on 62 audits were collected. Training in clinical governance was received by 55 auditors (89%) and a senior supervisor was available in 56 audits (90%). Audits were performed across different hospitals and specialties: 18 (29%) in obstetrics, 16 (26%) in medicine, and 11 (18%) in each of surgery and paediatrics, with six (10%) in other specialties. A clear trend of increasing numbers of audits was observed, with four (6%) having been done in 2015, 12 (19%) in 2016, 22 (35%) in 2017, and 24 audits (39%) in 2018. Students were involved in 46 audits (74%) whereas practising doctors were involved in only 29 audits (47%). 17 (27.4%) audits were done at more than one health-care facility and the remaining audits were done at one of 13 other main hospitals or community centres across the Gaza Strip. Clear standards were identified in 54 audits (90%) while eight audits (13%) reported not setting standards at all. Improvement of documentation was recommended in 44 audits (71%), development of national guidelines in 37 (60%), and staff training in 32 (52%). Only 32 audits (51.6%) were presented to the local staff. The audit cycle was completed in 13 projects (20.9%) with only seven of them reporting subsequent improvements in practice. Interpretation: A rise in the numbers of audits reflects a growing awareness of their key role in health care and patients' safety. However, completion of audit cycles and the actual implementation of recommendations are lagging. Therefore, more focused efforts supported by both clinical and administrative leaderships are needed to implement changes and ensure continuous evaluation of their effectiveness. Funding: None.